2008
DOI: 10.1159/000164687
|View full text |Cite
|
Sign up to set email alerts
|

Topological and Developmental Expression Gradients of Kir2.1, an Inward Rectifier K<sup>+</sup> Channel, in Spiral Ganglion and Cochlear Hair Cells of Mouse Inner Ear

Abstract: Objectives: Inwardly rectifying potassium current plays critical roles in setting resting membrane potential and thus modulating the excitability of many excitable cells including the hair cells in inner ears, which are excitable during early development. Up to 7 subfamilies have been identified as channels for this current. The present study investigated the developmental and spatial expression of one member, Kir2.1, in the sensorineural epithelia and spiral ganglion neurons of mouse cochleae starting from ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
15
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 78 publications
(58 reference statements)
6
15
0
Order By: Relevance
“…Consistent with previous studies (Géléoc et al 2004;Rüsch et al 1998), we observed strong inward rectifier currents throughout early development in mouse utricle type II hair cells. We used the whole-cell, tight-seal technique in voltage-clamp mode to record fast inward rectifier currents, which were evoked by a protocol that included hyperpolarizing voltage steps from a holding potential of Ϫ64 mV to potentials between Ϫ124 and Ϫ54 mV in increments of 10 mV.…”
Section: Inward Rectifier Currents In Utricle Hair Cellssupporting
confidence: 93%
See 4 more Smart Citations
“…Consistent with previous studies (Géléoc et al 2004;Rüsch et al 1998), we observed strong inward rectifier currents throughout early development in mouse utricle type II hair cells. We used the whole-cell, tight-seal technique in voltage-clamp mode to record fast inward rectifier currents, which were evoked by a protocol that included hyperpolarizing voltage steps from a holding potential of Ϫ64 mV to potentials between Ϫ124 and Ϫ54 mV in increments of 10 mV.…”
Section: Inward Rectifier Currents In Utricle Hair Cellssupporting
confidence: 93%
“…Small changes in the electrical properties of the basolateral membrane can modify the hair cell receptor potential and consequently, neurotransmitter release at the afferent synapse. These changes include the developmental acquisition of various ion channels required for proper modulation and transmission of the sensory signal, which continues until hair cells reach functional maturity, around postnatal day 8 (P8) (Rüsch et al 1998), as well as modulation by various efferent mechanisms. To extend an understanding of the functional development and the molecular components required for hair cell signaling, we focus here on the Kir2 family of potassium inward rectifier channels and their contributions to mammalian vestibular hair cell function.…”
mentioning
confidence: 99%
See 3 more Smart Citations